A monocrystal graphene domain biosensor array with differential output for real-time monitoring of glucose and normal saline. Issue 17 (8th April 2015) - Shi, Junjie; Li, Xin; Chen, Qian; Gao, Kun; Song, Hui; Guo, Shixi; Li, Quanfu; Fang, Ming; Liu, Weihua; Liu, Hongzhong; Wang, Xiaoli
Abstract : A biosensor array with differential output based on a monocrystal graphene domain is proposed to realize high resolution measurements. Abstract : A biosensor array with differential output based on a monocrystal graphene domain is proposed to realize high resolution measurements. The differential output structure can eliminate the noise that comes from graphene crystal orientation and grain boundary, as well as the fluctuation that comes from the contact resistance and experiment process, so as to improve resolution in the lower concentration. We have fabricated a high quality monocrystal graphene domain that has millimeter size by the chemical vapor deposition method. Two identical graphene ribbons that are cut from the same domain are used as field effect transistor source-to-drain channels for the reference and the test of differential output, respectively. The experimental results show that the source-to-drain current has a fast response shorter than 0.5 second in glucose, normal saline and pH buffer solutions of different concentrations. Sensitivity increases exponentially with the increase of concentration of the tested liquid and the high resolution range is 0.01–2 wt% in glucose and 0.0009–0.018 wt% in saline, and the highest resolutions of glucose and saline are 0.01 wt% and 0.0009 wt%, respectively. We have fabricated a 1 × 4 array structure with differential outputs that pave the way for rapidly detecting ultra-low concentration of analytes.